Valorization of Pepper Stalk Waste from Sebuluh Village into “Tabula Sebuluh” Mosquito Incense Sticks in the Indonesia–Malaysia Border Region - Chris Octavianus; Alexander Andi Kurnianto; Agustinus Marjun; Margareta Tessia; Novariana Masselli (International Journal of Public Devotion, 2026)
Sebuluh Village, located in Ketungau Hulu Subdistrict, Sintang Regency, is one of the pepper-producing areas with farmer groups that manage pepper gardens. The pepper harvesting process produces waste in the form of pepper stalks, which have not been utilized by farmers. Based on literature research and observation, it is known that pepper stalks contain piperine compounds that are effective in repelling mosquitoes. In addition, the abundant cassava plants in Sebuluh Village can be used as a filler and binder in the manufacture of mosquito repellent incense. This community service program aims to process pepper stalks into mosquito repellent incense that has economic value, as well as to improve the competence of members of the Sebuluh Pepper Farmers Group in waste management, production, and product marketing. Training and assistance were provided in the form of product processing, as well as the importance of branding and attractive packaging to increase sales. An evaluation of 19 participants using N-Gain yielded a score of 0.68, which falls into the moderate category, meaning that 52.6% of participants showed an increase in the competence of the Lada Sebuluh farmer group members. There is a need to improve understanding of product branding and packaging aspects. This program also contributes positively to environmental sustainability by reducing waste, utilizing local resources sustainably, and in the long term, improving the economy of farmer groups.Valorisasi Limbah Tangkai Buah Lada Desa Sebuluh Menjadi Racun Nyamuk Bakar “Tabula Sebuluh” di Wilayah Perbatasan Indonesia–MalaysiaABSTRAKDesa Sebuluh, yang terletak di Kecamatan Ketungau Hulu, Kabupaten Sintang, merupakan salah satu penghasil lada dengan kelompok tani yang mengelola kebun lada. Proses pemanenan lada menghasilkan limbah berupa tangkai buah lada yang selama ini tidak dimanfaatkan oleh petani. Berdasarkan penelitian literatur dan observasi, diketahui bahwa tangkai buah lada mengandung senyawa piperin yang efektif dalam mengusir nyamuk. Selain itu, tanaman singkong yang melimpah di desa Sebuluh dapat dimanfaatkan sebagai bahan pengisi dan pengikat dalam pembuatan produk racun nyamuk bakar. Program pengabdian ini bertujuan untuk mengolah limbah tangkai buah lada menjadi racun nyamuk bakar yang bernilai ekonomi, serta meningkatkan kompetensi anggota kelompok tani Lada Sebuluh dalam pengelolaan limbah, produksi, dan pemasaran produk. Pelatihan dan pendampingan diberikan dalam bentuk pengolahan produk, serta pentingnya branding dan pengemasan yang menarik untuk meningkatkan daya jual. Evaluasi yang dilakukan terhadap 19 peserta dengan menggunakan N-Gain mendapatkan skor 0,68 dan termasuk dalam kategori sedang, atau 52,6% peserta menunjukkan peningkatan kompetensi anggota kelompok tani Lada Sebuluh. Terdapat kebutuhan untuk meningkatkan pemahaman mengenai aspek branding dan pengemasan produk. Program ini juga memberikan kontribusi positif terhadap kelestarian lingkungan dengan mengurangi limbah, memanfaatkan sumber daya lokal secara berkelanjutan serta jangka panjangnya dapat meningkatkan ekonomi kelompok tani.Kata Kunci :Racun nyamuk bakar; tangkai buah lada; fitokimia; Sebuluh